Upaya Meningkatkan Aktivitas dan Hasil Belajar Spektrofotometri UV Vis Dengan Model Pembelajaran Direct Instruction - Sriyati Sriyati (Jurnal Pendidik Indonesia (JPIn), 2022)
The low level of student skills in using the equipment used during the practicum, namely UV Vis Spectrophotometry equipment. This study aims to determine the process and results of applying the Direct Instruction learning model or direct learning to increase activity and learning outcomes of UV Vis Spectrophotometry material in class XI APL 1 SMK Negeri 1 Cangkringan. The subjects of this study were students of class XI APL 1, totaling 36 student. This study consisted of 2 cycles, each cycle held a reflection so that the activities and student learning outcomes can be seen. The instruments used in this study consisted of non-test instruments and test instruments. The results showed an increase in activity and learning outcomes of Chemical Analysis Instruments UV Vis Spectrophotometry. Increased activity and student learning outcomes can be seen from the first cycle to the second cycle, namely in the first cycle the class learning completeness does not meet the criteria and in the second cycle the learning completeness meets the criteria. Thus, after undergoing the Direct Instruction action process there was an increase in student activity and learning outcomes.